2022
DOI: 10.3390/su142114331
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Accessibility of Community Sports Facilities in Fuzhou, China

Abstract: With the coordinate data of community sports facilities in Fuzhou and the Geographic Information System platform, this paper developed a research framework of accessibility from three aspects of distribution, service coverage and access equality level. In addition, based on this, this paper analyzed the level and characteristics of the accessibility of community sports facilities within the third ring road of Fuzhou, China. The results showed that the community sports facilities within the third ring road of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The government has spent much money enhancing and expanding the country’s sporting facilities. China has made great strides in providing public areas for sports and recreation, from state-of-the-art stadiums and arenas to neighborhood recreation centres and public parks [ 36 ]. The country has also prioritized upgrading sports infrastructure in K-12 and higher education institutions, viewing sports as essential to a well-rounded education [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The government has spent much money enhancing and expanding the country’s sporting facilities. China has made great strides in providing public areas for sports and recreation, from state-of-the-art stadiums and arenas to neighborhood recreation centres and public parks [ 36 ]. The country has also prioritized upgrading sports infrastructure in K-12 and higher education institutions, viewing sports as essential to a well-rounded education [ 37 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As an integration of sports and leisure facilities and ecological gardens, sports parks have been playing a key role in public health and the national strategy of Healthy China by providing sports avenues to urban residents, thereby enhancing their quality of life [ 3 , 4 ]. However, existing sports parks in China exhibit poor spatial distribution and low accessibility owing to absences of studies and guidance in this field, resulting in low utilization rate [ 5 , 6 ]. In recent years, an increasing population of urban residents have been concerned about accessibility to sports parks and services, namely sharing of eco-sports resource by the public.…”
Section: Introductionmentioning
confidence: 99%
“…In [29], a method for eliminating interference due to the resistive current of an MOA based on adaptive variational mode decomposition and adaptive singular value decomposition was proposed. Mathematical morphological filters were used in [34] to denoise the on-site monitoring signal of an MOA leakage current with a strong interference background. In [35], on-line monitoring of the full current and temperature and humidity variations of surge arresters was carried out, and it was concluded that these variations have some correlation in field tests.…”
Section: Introductionmentioning
confidence: 99%